2019
DOI: 10.2147/ott.s192137
|View full text |Cite|
|
Sign up to set email alerts
|

<p>microRNA-628 inhibits the proliferation of acute myeloid leukemia cells by directly targeting IGF-1R</p>

Abstract: BackgroundA variety of microRNAs (miRNAs) are aberrantly expressed in acute myeloid leukemia (AML), and these dysregulated miRNAs perform crucial roles in tumorigenesis and progression of AML. miR-628-3p (miR-628), one of the miRNAs dysregulated in multiple types of human cancers, exerts antitumor roles in different cancer types. However, no specific study has explored the expression pattern and role of miR-628 in AML.Materials and methodsIn this study, RT-qPCR was performed to detect miR-628 expression in AML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In recent years, miR-628-3p (miR-628) was reported to substantially participate in the progression of several types of human cancer, including colorectal cancer,20 acute myeloid leukemia,21 pancreatic cancer,22 and non-small-cell lung cancer 23. Nevertheless, whether the expression profile of miR-628 is altered in gastric cancer remains unclear and whether its aberrant expression is important for the aggressiveness of gastric cancer is yet to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, miR-628-3p (miR-628) was reported to substantially participate in the progression of several types of human cancer, including colorectal cancer,20 acute myeloid leukemia,21 pancreatic cancer,22 and non-small-cell lung cancer 23. Nevertheless, whether the expression profile of miR-628 is altered in gastric cancer remains unclear and whether its aberrant expression is important for the aggressiveness of gastric cancer is yet to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was hypothesized that mir-628-5p is a tumor suppressor for colorectal cancer. mir-628-5p decreased the tumorigenicity of epithelial ovarian cancer cells (44), and mirna-628 inhibited the proliferation of acute myeloid leukemia cells (14). in addition, mir-628 .…”
Section: Ccnd1 Is Required For the Proliferation And Apoptosis Of Ht-mentioning
confidence: 96%
“…Previous studies have demonstrated that mirnas serve an important role in the development of tumors; the aberrant overexpression or downregulation of multiple mirnas are often detected in a variety of tumors, suggesting that mirnas have different roles in different processes, such as tumor occurrence, development and metastasis (11,12). Previous studies have reported the abnormal expression of mirna (mir)-628 in numerous malignant tumor tissues (13,14); however, there are few studies observing the effects of mir-628 in colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, PTEN plays critical roles in regulating not only hematopoietic stem cell activity through a Niche-dependent mechanism, but also hematopoiesis and leukemogenesis [341][342][343]. Furthermore, TAL1, c-Jun, EZH2, TRIM22, ETV6/RUNX1, miR-7, -22, -26b, -103, -125b, -126, -139-5p, -181c, -193a, -628, and -3142, as well as LncRNA HULC, UCA1, linc00239 and LINC00265 control leukemogenesis, proliferation, apoptosis or chemoresistance via PI3K/AKT pathway [344][345][346][347][348][349][350][351][352][353][354][355][356][357][358][359][360][361][362][363]. Hereafter, PI3K/AKT pathway inhibition is regarded as a therapeutic approach [364,365] followed by the preclinical studies in leukemia cells [366,367] in spite of the upregulated expression of P2RY14 in acute leukemia cells resistant to PI3K/ mTOR inhibition [368].…”
Section: (Nct01002248; Nct01476137; Nct00881946) (Tables 2 and 3)mentioning
confidence: 99%